بيداغوجيا الخطإ في الممارسة التعليمية التعليمية الحديثة - بن علي, فيصل (جامعة الوادي - University of Eloued, 2021)
ملخص: إنّ نجاح العملية التّعليميّة مرهون بمدى تكامل أنشطتها كما تؤكد ذلك المناهج التّربويّة الحديثة، ولعل أهم نشاط في كل وضعيّة تعليميّة تعلّميّة مهما كان نوعها هو التّقييم والتّقويم؛ فمن خلالهما يستطيع المعلّم مسايرة التّعلم وتصويب التّعلّمات بدقّة لكي يحقّق الكفاءات المستهدفة من كل درس، وهو في ذلك يحاول تتبّع الأخطاء ومعالجتها في كلّ خطوة تعليميّة. ومن هذا المنطلق، فقد أضحى الخطأ البيداغوجي أحد أهم المفاهيم التي تتمتع بمكانة خاصة داخل المنظومة التّعليميّة الحديثة بعد أن كان مصدر قلق ومؤشر فشل في العمليّة التّعليميّة، ومع تغيّر النّظرة إليه بين القديم والحديث، فقد أعيد الاهتمام به وبأهم قضاياه، حيث أصبح للخطإ بيداغوجيا خاصّة به، ووظائف تعليميّة، وطرائق علاجيّة باعتباره مصدرا إيجابيا في المسار التّعليمي التّعلمي، لا عاملا أساسيا من عوامل الفشل والإرباك الدّراسي نظرا لارتباطه بدلالة سلبيّة. الكلمات المفتاحية: وضعية تعليمية تعلّميّة- تقييم- تقويم- بيداغوجيا- خطأ. Abstract: The success of the educational process depends on the extent of the integration of its activities, as confirmed by modern educational curricula. Perhaps the most important activity in every educational situation is evaluation; Through it, the teacher can discover mistakes and correct them step by step, so making mistakes is an important stage in building new knowledge. From this point of view, pedagogical error has become one of the most important concepts that enjoys a special place within the modern educational system after it was a source of concern and an indicator of failure in the educational process, and with the change in the view of error between ancient and modern pedagogy, attention has been restored to it and its most important issues, where error has become a pedagogy. Its own, educational functions, and remedial methods as a positive source in the educational-learning path, not a major factor of academic failure and confusion. Key words: Educational situation - evaluation - pedagogical error.
مقال
Keywords: تقييم- ; تقويم ; بيداغوجيا ; خطأ ; وضعية تعليمية تعلمية